20-Gauge vs. 23-Gauge Vitrectomy, in Terms of Surgically Induced Astigmatism - Muhammad Tariq Khan; Shafqat Ali Shah; Kaleem Ullah; Muhammad Bilal (Gandhara University, 2023)
OBJECTIVES To compare the post-operative (post-op) surgically induced mean astigmatism in patients undergoing 20-gauge- and 23-gauge vitrectomy. METHODOLOGY Sixty patients were enrolled. Relevant information was recorded in a Performa for each patient. Patients were randomly grouped into A (20-gauge) and B (23-gauge) groups. Astigmatism was recorded by a single technician using the same keratometer for all patients. A single surgeon operated on all patients. Post-operatively, all patients were re-examined after 1 week and 6 weeks, and their surgically induced astigmatism was recorded. RESULTS Of 60 patients, 58.6% were males, and 41.4% were females, with a mean age of 53.77 ± 9.63 years. The post-operative astigmatism difference between the two vitrectomy procedures was investigated. In the 20-gauge group, with 30 patients, the mean post-operative astigmatism difference was 2.21 D (±0.66 SD), with a standard error mean of 0.12. In the 23-gauge group, with 30 patients, the mean post-operative astigmatism difference was 0.74 D (±0.44 SD), with a standard error mean of 0.08. The degrees of freedom (df) were 58, and the standard error of the difference was 0.145. The t-value was calculated at 10.1504, and the p-value was found to be 0.001, indicating a significant difference. CONCLUSION The observation that the 20-gauge group displayed a notably higher mean difference in astigmatism than the 23-gauge group suggests a potential association between the choice of vitrectomy procedure and the extent of astigmatism alteration in post-operative outcomes.